First National Genomic Epidemiological Study of Neisseria gonorrhoeae Strains Spreading Across Sweden in 2016 - Hadad, Ronza; Golparian, Daniel; Velicko, Inga; Ohlsson, Anna-Karin; Lindroth, Ylva; Ericson, Eva-Lena; Fredlund, Hans; Engstrand, Lars; Unemo, Magnus (Frontiers in Microbiology, 2022)
The increasing transmission and antimicrobial resistance (AMR) in Neisseria gonorrhoeae is a global health concern with worrying trends of decreasing susceptibility to also the last-line extended-spectrum cephalosporin (ESC) ceftriaxone. A dramatic increase of reported gonorrhoea cases has been observed in Sweden from 2016 and onwards. The aim of the present study was to comprehensively investigate the genomic epidemiology of all cultured N. gonorrhoeae isolates in Sweden during 2016, in conjunction with phenotypic AMR and clinical and epidemiological data of patients. In total, 1279 isolates were examined. Etest and whole-genome sequencing (WGS) were performed, and epidemiological data obtained from the Public Health Agency of Sweden. Overall, 51.1%, 1.7%, and 1.3% resistance to ciprofloxacin, cefixime, and azithromycin, respectively, was found. No isolates were resistant to ceftriaxone, however, 9.3% of isolates showed a decreased susceptibility to ceftriaxone and 10.5% to cefixime. In total, 44 penA alleles were found of which six were mosaic (n=92). Using the typing schemes of MLST, NG-MAST, and NG-STAR; 133, 422, and 280 sequence types, respectively, and 93 NG-STAR clonal complexes were found. The phylogenomic analysis revealed two main lineages (A and B) with lineage A divided into two main sublineages (A1 and A2). Resistance and decreased susceptibility to ESCs and azithromycin and associated AMR determinants, such as mosaic penA and mosaic mtrD, were predominantly found in sublineage A2. Resistance to cefixime and azithromycin was more prevalent among heterosexuals and MSM, respectively, and both were predominantly spread through domestic transmission. Continuous surveillance of the spread and evolution of N. gonorrhoeae, including phenotypic AMR testing and WGS, is essential for enhanced knowledge regarding the dynamic evolution of N. gonorrhoeae and gonorrhoea epidemiology.